2017
DOI: 10.1038/s41598-017-16785-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding data unveils invisible pollination networks

Abstract: Animal pollination, essential for both ecological services and ecosystem functioning, is threatened by ongoing global changes. New methodologies to decipher their effects on pollinator composition to ecosystem health are urgently required. We compare the main structural parameters of pollination networks based on DNA metabarcoding data with networks based on direct observations of insect visits to plants at three resolution levels. By detecting numerous additional hidden interactions, metabarcoding data largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 62 publications
3
102
0
1
Order By: Relevance
“…However, 27.8% and 43.9% of insects were captured when foraging on the shrub in the low‐density LDP1 and LDP2 patches and 41.6% and 41.9% in the high‐density HDP1 and HDP2 patches, respectively. Thus, as previously demonstrated (Pornon et al, ) metabarcoding unveiled many links that existed both outside the study plots and before the capture, which therefore could not be observed during the visit surveys. Despite being visited by a broad array of insect species (sp‐sp N link ), R. ferrugineum was abundant only in the pollen loads of Apis mellifera , Bombus lucorum , and B. pratorum (Figure ).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…However, 27.8% and 43.9% of insects were captured when foraging on the shrub in the low‐density LDP1 and LDP2 patches and 41.6% and 41.9% in the high‐density HDP1 and HDP2 patches, respectively. Thus, as previously demonstrated (Pornon et al, ) metabarcoding unveiled many links that existed both outside the study plots and before the capture, which therefore could not be observed during the visit surveys. Despite being visited by a broad array of insect species (sp‐sp N link ), R. ferrugineum was abundant only in the pollen loads of Apis mellifera , Bombus lucorum , and B. pratorum (Figure ).…”
Section: Resultsmentioning
confidence: 55%
“…in the grassland matrices and as wind‐pollinated plants usually produce far more abundant airborne pollen than insect‐pollinated plants, grasses should represent a level of widespread background contamination that insect‐pollinated plants would barely, if ever, reach. In a previous study (Pornon et al, ), we observed that the 1,000 sequence threshold allowed the removal of more than 95% of grass sequences, and under all hypotheses, also removed all potential contamination originating from insect‐pollinated plants. From i ‐sp M seq and i ‐sp M link , we analyzed the following: (a) individual and species pollination networks and (b) individual and species food niches.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Another recent study comparing pollen metabarcoding with observation of flower visits found that metabarcoding revealed 2.5 times more plant species (Pornon et al., 2016). While some of these species may have been detected from very small quantities of pollen or DNA including contact contamination in nature and therefore not represent preferred plant species; overall, the increase in resolution is extremely valuable in providing more detailed insight into foraging patterns (Pornon et al., 2017). In a small number of cases, DNA based approaches have been incorporated into interaction networks and have demonstrated that this new level of resolution can provide dramatic changes in network metrics (Wirta et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding has helped to reveal the full complexity of tropical plant-herbivore food webs and how the level of specialization varies between feeding guilds (Novotny et al, 2010). For instance, metabarcoding technology has shown that pollinators are much more generalist than expected from visit surveys (Pornon et al, 2017). In addition to traditional Sanger sequencing, the use of NGS amplicon sequencing allows the parallel acquisition of DNA barcodes from hundreds of specimens and the characterization of communities of both insects and their associated microbial symbionts simultaneously .…”
Section: Future Promises and Challengesmentioning
confidence: 99%